Hadis Tentang Gadai: Analisis Hukum Pemanfaatan Hewan sebagai Barang Jaminan oleh Murtahin - Doli Witro; Arzam Arzam; Mhd. Rasidin (Jurnal Hukum Ekonomi Syariah, 2021)
Tulisan ini membahas hadis yang berkenaan dengan hukum gadai. Pembahasan dalam tulisan ini dikhususkan dalam sebuah hadis yang ditetapkan sebagai hadis utama. Kemudian hadis akan diuraikan dari teks, artinya, tafsir, hal-hal penting yang terdapat dalam hadis, perbedaan pendapat para ulama, kandungan hadis, dan faedah yang terdapat dalam hadis tersebut. Dalam pemaparan hadis tersebut ditambah juga dengan hadis-hadis lain yang menjelaskan tentang gadai sebagai penguat. Tulisan ini bertujuan menjelaskan hukum barang gadai yang dimanfaatkan oleh penerima gadai. Artikel ini menggunakan penelitian kualitatif yang bersifat pustaka. Bahan-bahan dalam penelitian ini diambil dari bahan pustaka seperti buku dan artikel ilmiah yang diterbitkan di jurnal yang berkaitan dengan permasalahan yang dibahas yaitu tentang hukum gadai. Teknik analisis yang digunakan yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Analisis menunjukkan barang (jaminan) yang digadai kepada seorang penerima gadai boleh dimanfaatkan selama dia membayar sewa dari manfaat yang diambilnya. Hadith About Pawn: Legal Analysis of the Use of Animals as Collateral by Murtahin AbstractThis paper discusses the hadiths relating to the law of pawning, especially the use of pawning items by mu. The discussion in this paper is devoted to a hadith, which is designated as the main hadith. Then the hadith will be elaborated from the text, its meaning, interpretation, important matters contained in the hadith, differences in opinion of the scholars, the content of the hadith, and the benefits contained in the hadith. In the explanation of the hadith, other traditions that explain pawning as reinforcement are also added. This paper aims to explain the law of pawn items used by pawn recipients (murtahin). This article uses qualitative research that is the library in nature. The materials in this study were taken from library materials such as books and scientific articles published in journals related to the issues discussed, namely the law of using pawn items by murtahin. The analysis technique used is data reduction, data presentation, and conclusion drawing. The results of the analysis show that the goods (collateral) that are pawned to a pledge recipient can be used as long as he pays the rent from the benefits he takes. Keywords: Pawn Hadith; Pawn Law; Utilization of Pawn Goods